Perforated Duodenal Ulcer in Pregnancy-A Rare Cause of Acute Abdominal Pain in Pregnancy: A Case Report and Literature Review - Papa Essilfie; M. Hussain; I. Bolaji (Hindawi Limited, 2011)
Medical and surgical disorders in pregnancy can be can be quite challenging for the obstetrician gynaecologist even in resource rich countries. Reaching an accurate diagnosis and admininstering appropriate management can be difficult in the presence of an on-going pregnancy. The importance of involving specialist from other disciplines (multidisciplinary care) cannot be overemphasized. We present an interesting case of perforated duodenal ulcer in a pregnant patient, review the literature ,discuss the differential diagnosis and evaluate the management principles for this rare condition.